Vínculos organizacionais e comportamentos de cidadania organizacional para o meio ambiente: um estudo com os servidores da UFSM - Cristo, Elenara Milena de (2024)
Organizational Behavior studies how employees behave in organizations, and one of its themes is Organizational Bonds, such as Commitment, which is the emotional attachment of workers to the company, Consent, which is the employee's permanence out of obligation, loaded the thought of duty towards the organization, and Entrenchment, which is when the employee continues in the organization out of their own need. Another topic covered in Organizational Behavior is Organizational Citizenship Behavior for the Environment (CCO-MA). In CCO-MA, it is understood that there is a connection between environmental efforts and employees' CCO, highlighting the importance of these attitudes in the environmental context. The Federal University of Santa Maria (UFSM) has strong involvement in sustainable practices and sustainability rankings, however, it is not yet known whether the employees of this public institution have the CCO-MA in their behaviors, and whether this is influenced by the links that they have with the institution. Therefore, this study highlights the need to investigate the themes together, exploring unaddressed relationships between the links of Consent and Entrenchment with the CCO-MA, and also the relationship between Commitment and the CCO-MA, already addressed in the literature. Therefore, it is pertinent to determine the influence that Organizational Links have on CCO-MA in UFSM Servers. To this end, research with a descriptive and explanatory approach was carried out, with a quantitative method. The scales by Bastos and Aguiar (2015), Silva and Bastos (2015), Rodrigues and Bastos (2015), and Boiral and Poillé (2012) were used, in their translated and adapted version by Costa et al. (2022), in the construction of the questionnaires applied to 440 employees of the institution. For the analysis of the study, structural equation modeling techniques were used. The study's respondents were primarily between 31 and 40 years old, female, married, with a postgraduate degree, working at UFSM for a period of 6 to 10 years in the category of Administrative Techniques in Education, without a position of Management/Leadership and linked to the Center for Social and Human Sciences (CCSH). High levels of Commitment and CCO-MA were evident, while Consent and Entrenchment were moderate. It was identified that the links of Organizational Commitment and Organizational Entrenchment have a positive influence on the CCO-MA. However, the Organizational Consent link did not demonstrate the same influence. It was found that the profile variables gender and category of server moderate the influence of Entrenchment on the CCO-MA of UFSM employees, but the variables age, education, marital status and length of service do not. The main limitations are the context in which the study was carried out, with public servants from a Federal Higher Education Institution being a very specific audience, in addition to the majority of respondents being TAE’s and working at the UFSM headquarters campus.